ANALISIS PENGARUH GCG, EARNINGS MANAGEMENT, DAN SUKU BUNGA TERHADAP PROFITABILITAS PERBANKAN BUMN YANG TERDAFTAR DI BEI - Rizki Syah Putra; Freska Kristiana; Harun Al Fauzan; Intan Dara Permata; Dinna Ayu Sekarwangi (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This study is designed to evaluate the impact of Good Corporate Governance (GCG) implementation, earnings management behavior, and fluctuations in the Bank Indonesia benchmark interest rate on the profitability of state-owned enterprise (BUMN) banks listed on the Indonesia Stock Exchange over the period from 2017 to 2024. In this research, GCG quality is proxied by the Corporate Governance Perception Index (CGPI) score, while earnings management activities are identified using the Modified Jones Model to estimate discretionary accruals. Banking financial performance, specifically profitability, is proxied by the Return on Assets (ROA) ratio as the dependent variable. To test the hypotheses, the study analyzes panel data sourced from the four largest state-owned banks (Mandiri, BRI, BNI, and BTN) utilizing a Fixed Effect regression model approach. To mitigate potential bias in error variance, the estimation model is reinforced with the clustered robust standard error technique. Simultaneous statistical testing confirms that all included predictor variables collectively exert a significant influence in explaining the variation in bank ROA levels. However, partial testing highlights that only earnings management has a positive and significant impact on profitability. Conversely, the GCG and benchmark interest rate variables do not demonstrate a statistically significant effect. This phenomenon suggests that the surge in state-owned bank profitability during the observation period was driven more by managerial discretion in earnings reporting than by governance effectiveness or external macroeconomic conditions.